Substance abuse among Adolescents and Youth (10–24 years): Assessing the prevalence and risk assessment in the suburban areas of Dehradun District, Uttarakhand - Jayanti Semwal; Deepshikha; Vidhisha Vallabh; Akanksha Uniyal; Ashok Shrivastava; Rajeev Bijalwan; Deepti Nagrath (Journal of Family Medicine and Primary Care)
Introduction: Substance abuse issues are identified, in Uttarakhand, despite limited and outdated data. Thus, our study aims to assess the risk and prevalence of substance abuse (alcohol, tobacco, cannabis, cocaine, opioids, amphetamines, inhalants, sedatives, and hallucinogens) among teenagers and young people in the suburbs of Dehradun district of Uttarakhand. Methods: A survey was conducted among 14,203 individuals aged 10–24 from Doiwala Block (6023 participants) and Sahaspur Block (8180 participants). The survey included participants from the community and schools/colleges and used the CRAFT and ASSIST questionnaire to establish risk scores for different drugs. Results: In Doiwala block, the overall prevalence of substance use was 13.02%. The Risk Scoring for CRAFFT revealed that 58% of the 64 participants showed a high degree of risk of substance abuse. In Sahaspur Block, the overall prevalence of substance use was 8.14%. Among 10–17 years individuals (n = 107) using the CRAFFT questionnaire, 30% scored more than or equal to 2, which reflected a high potential risk. Discussion: The growing epidemic of substance abuse is preventable in the community with collective efforts of the society, law enforcement department, community leaders, ASHA workers, school teachers, and health personnels. The best platform to achieve a difference in the community is at the school level, where the adolescents spend 6–7 hours of their time every day. Conclusion: Addiction treatment programs that heavily emphasize inpatient treatment or hospitalization in addiction centers are unlikely to be able to keep up with the tremendous increase in the prevalence of substance abuse.